2007
DOI: 10.1111/j.1469-8986.2007.00604.x
|View full text |Cite
|
Sign up to set email alerts
|

The skin conductance orienting response to semantic stimuli: Significance can be independent of arousal

Abstract: The characteristics of stimuli that elicit skin conductance responses (SCRs) have been conceptualized in varied ways, with strong emphasis on the significance or arousing quality of stimuli. Our goal was to determine whether "significance" can be shown to have an effect on SCRs independent of "arousal," using words as stimuli. Ratings of words indicated that significance is partially independent of arousal. In Study 1, SCRs from 43 participants during presentation of 20 significant, nonarousing words with a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Hence, one may speculate that the present findings are specific to the CIT paradigm. However, as more evidence has been accumulated over time, only the SCR consistently showed the expected effects of novelty, intensity, and significance (e.g., Barry, ; Dindo & Fowles, ). Specifically, while some studies found the HR to decelerate in response to novel stimuli (e.g., Bradley, ; Siddle & Turpin, ), others found the HR to be insensitive to stimulus novelty (Barry, ; Barry & James, ; Barry & Maltzman, ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, one may speculate that the present findings are specific to the CIT paradigm. However, as more evidence has been accumulated over time, only the SCR consistently showed the expected effects of novelty, intensity, and significance (e.g., Barry, ; Dindo & Fowles, ). Specifically, while some studies found the HR to decelerate in response to novel stimuli (e.g., Bradley, ; Siddle & Turpin, ), others found the HR to be insensitive to stimulus novelty (Barry, ; Barry & James, ; Barry & Maltzman, ).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence in non‐musical domains showed that the relevance of the task for a given subject plays a role in modulating the SCR (Dindo & Fowles, 2008; Epstein & Fenz, 1962; Fenz & Epstein, 1962; Lang et al, 1998; Ohman & Soares, 1994; Perpina, Leonard, Bond, Bond, & Banos, 1998; Stormark, Laberg, Nordby, & Hugdahl, 2000). These studies, carried out with psychiatric patients and normal volunteers, revealed that higher SCRs specific to a given object were dependent on individual experience.…”
Section: Discussionmentioning
confidence: 99%
“…Both positive mood induction procedures aimed at elevating the current mood, but by completely different means. Skin conductance is known to be related to arousal and strongly reacts to novelty; [23], [24] the mood induction procedure via cartoons confronted our participants with new and potentially arousing emotional stimuli, which might explain elevated skin conductance. Diminished SCRs in the happy mood induction might have been brought about by habituation to the rather invariant facial stimuli, self-paced presentation and the comparatively rather constant and more steady mood state reached by intentional attempts to get into the mood via autobiographical imagination [23], whereas in the cartoon condition, the mood change was much more stimulus driven and largely dependent upon emotional reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Somatic markers contribute emotional activation to cognitive processing and have primarily been introduced into decision making using skin conductance as physiological measure of somatic marker activity. Skin conductance generally relates to arousal and reacts to novelty of a stimulus [23], [24] as well as to omission of an expected stimulus [25]. Emotional, significant or intense stimuli also commonly result in elevated skin conductance responses (SCR) [24].…”
Section: Introductionmentioning
confidence: 99%